Ехокардиографски и клинички карактеристики на дијабетичната кардиомиопатија - Митровска, Славица (Медицински факултет, УКИМ, Скопје, 2017)
Background: Diabetic cardiomyopathy is defined as heart failure independent of coronary artery, valve disease and hypertension. It has multifactorial etiology but the pathogenesis is incompletely understood. Hyperglycemia, hyperlipidemia and inflammation with high oxidative stress lead to structural and functional alterations of the left ventricle (LV) and promote diabetic cardiomyopathy. Diastolic dysfunction is an early sign of diabetic cardiomyopathy. It has long asymptomatic period, but with time leads to loss of contractile function. Hence, the identification of subclinical diabetic cardiomyopathy and correction of potentially modified risk factors are very important in order to delay onset of heart failure. The aim: We aimed to assess the LV function in asymptomatic diabetic patients and its correlation with clinical and biochemical parameters. Study design: Cross-sectional study that include total number of 137 subjects. The target group consists of 72 asymptomatic normotensive patients with diabetes mellitus type 2, without coronary artery and valve diseases. The control group is composed of 65 apparently healthy subjects. Because diastolic dysfunction is very common in individuals older than 70 years, the participants were in timeframe of 30 to 65 years of age. Methods: All patients were subject to echocardiography (conventional 2D, M-mode, PW Doppler analysis and contemporary techniques-TDI and 2D-Speckle-Tracking Echocardiography). We assessed the correlation between echocardiographic parameters and clinical (age, gender, BMI, BSA, waist to hip ratio, duration of diabetes) and biochemical analyses (glucose profile, lipid profile, CRP) by Pearson Product Moment of Correlation. A p-value of <0.05 was considered to indicate significance. Results: Analysis of deformation identify the greatest number of subjects with abnormal myocardial mechanics (n=45, 62%), compared to other echocardiographic techniques PDA (n=34, 47%) and TDA (n=40, 56%). We noted statistically significant difference between the groups regarding the LV dysunction, in each imaging modality-PWD, TDI (Z=2.3, p=0.01; Z=2.9, p=0.003). There were strong negative correlations between clinical, biochemical and echocardiographic parameters of PW Doppler and 2D Speckle-Tracking Echocardography, and strong positive correlations with TDI. Conclusion: Doppler echocardiography is valuable imaging technique for identifying LV dysfunction in asymptomatic patients with diabetes, and is important part of diagnostic algoritam in diabetes cardiomyopathy. Novel Doppler-echocardiographic techniques as Tissue Doppler Imaging and Speckle-Tracking Echocardiography show superiority over other echocardiographic methods, regarding the early detection of LV functional abnormalities in asymptomatic diabetic population. Its introduction in daily routine will contribute to the timely initiation of treatment of risk factors, in order to prevent development of heart failure.
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Силвана Јованова.
Keywords: Diabetic cardiomyopathy, Diabetes mellitus, Left ventricular dysfunction, Tissue Doppler Imaging, Strain analysis